EVALUASI KEBIJAKAN PENGEMBANGAN SUMBER DAYA MANUSIA TEKNOLOGI INFORMASI DALAM PENERAPAN SISTEM INFORMASI MANAJEMEN - Feiza Aurelita; Sufian Hamim; Dia Meirina Suri; Raden Imam Al Hafis (Journal of Innovative and Creativity (Joecy), 2026)
The rapid advancement of information technology requires organizations to optimize the implementation of Management Information Systems (MIS) to improve organizational effectiveness and efficiency. The success of MIS implementation is determined not only by the availability of technological infrastructure but also by the quality of Information Technology (IT) human resources responsible for managing and operating the system. Therefore, policies for the development of IT human resources play a crucial role and need to be evaluated to ensure the achievement of organizational objectives. This study aims to evaluate the policy of Information Technology human resource development in the implementation of Management Information Systems, identify supporting and inhibiting factors in its implementation, and formulate recommendations for improving policy effectiveness. The evaluation is conducted using a public policy evaluation approach that focuses on aspects of effectiveness, efficiency, adequacy, responsiveness, and appropriateness of the policy. The research employs a qualitative approach with an evaluative research design. Data are collected through in-depth interviews, observations, and document analysis involving stakeholders responsible for IT human resource development and Management Information System implementation. Data analysis is carried out descriptively to examine the implementation of the policy and assess its alignment with the established objectives. The findings of this study are expected to provide a comprehensive overview of the effectiveness of IT human resource development policies in supporting the implementation of Management Information Systems. Furthermore, the results are anticipated to serve as a reference for policymakers in formulating more adaptive human resource development strategies that align with technological advancements and organizational needs.